Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Discover precise answers to your questions from a wide range of experts on our user-friendly Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Let's go step by step to solve each part of the algebra problem.
### 2.1 Algebraic Expression:
Given the expression:
[tex]\[ 4x^4 - x^3 + 5x^2 - 2x + 9 \][/tex]
#### 2.1.1. Write down the number of terms in the expression.
The expression \(4x^4 - x^3 + 5x^2 - 2x + 9\) has 5 terms.
#### 2.1.2. What is the coefficient of \(x^3\)?
The coefficient of \(x^3\) in the expression \(4x^4 - x^3 + 5x^2 - 2x + 9\) is \(-1\).
#### 2.1.3. Write down the constant term.
The constant term in the expression \(4x^4 - x^3 + 5x^2 - 2x + 9\) is 9.
#### 2.1.4. What is the degree of the expression?
The degree of the expression \(4x^4 - x^3 + 5x^2 - 2x + 9\) is determined by the highest power of \(x\), which is 4.
#### 2.1.5. What is the value of the expression when \(x=2\)?
Substitute \(x = 2\) into the expression:
[tex]\[ 4(2)^4 - (2)^3 + 5(2)^2 - 2(2) + 9 = 81 \][/tex]
So, the value of the expression when \(x=2\) is 81.
### 2.2. Solve for \(x\) in the equations below.
#### 2.2.1. \(2x = 88\)
To solve for \(x\):
[tex]\[ x = \frac{88}{2} = 44 \][/tex]
So, \(x = 44\).
#### 2.2.2. \(3x + 4 = 34\)
To isolate \(x\):
[tex]\[ 3x + 4 = 34 \implies 3x = 34 - 4 \implies 3x = 30 \implies x = \frac{30}{3} = 10 \][/tex]
So, \(x = 10\).
#### 2.2.3. \(4(x + 2) = 3(x + 2)\)
Let's simplify and solve for \(x\):
[tex]\[ 4(x + 2) = 3(x + 2) \implies 4 = 3 \][/tex]
There is no value of \(x\) that makes this equation true, so there is no solution.
#### 2.2.4. \(\frac{x}{3} + 2 = 5\)
To solve for \(x\):
[tex]\[ \frac{x}{3} + 2 = 5 \implies \frac{x}{3} = 5 - 2 \implies \frac{x}{3} = 3 \implies x = 3 \times 3 = 9 \][/tex]
So, \(x = 9\).
#### 2.2.5. \(3^x = 81\)
To solve for \(x\), note that \(81 = 3^4\):
[tex]\[ 3^x = 3^4 \implies x = 4 \][/tex]
So, \(x = 4\).
### 23. The sum of a number and 7 is 76. What is the number?
Let the number be \(y\). According to the problem:
[tex]\[ y + 7 = 76 \implies y = 76 - 7 = 69 \][/tex]
So, the number is 69.
This completes the step-by-step solution to the given algebra problem.
### 2.1 Algebraic Expression:
Given the expression:
[tex]\[ 4x^4 - x^3 + 5x^2 - 2x + 9 \][/tex]
#### 2.1.1. Write down the number of terms in the expression.
The expression \(4x^4 - x^3 + 5x^2 - 2x + 9\) has 5 terms.
#### 2.1.2. What is the coefficient of \(x^3\)?
The coefficient of \(x^3\) in the expression \(4x^4 - x^3 + 5x^2 - 2x + 9\) is \(-1\).
#### 2.1.3. Write down the constant term.
The constant term in the expression \(4x^4 - x^3 + 5x^2 - 2x + 9\) is 9.
#### 2.1.4. What is the degree of the expression?
The degree of the expression \(4x^4 - x^3 + 5x^2 - 2x + 9\) is determined by the highest power of \(x\), which is 4.
#### 2.1.5. What is the value of the expression when \(x=2\)?
Substitute \(x = 2\) into the expression:
[tex]\[ 4(2)^4 - (2)^3 + 5(2)^2 - 2(2) + 9 = 81 \][/tex]
So, the value of the expression when \(x=2\) is 81.
### 2.2. Solve for \(x\) in the equations below.
#### 2.2.1. \(2x = 88\)
To solve for \(x\):
[tex]\[ x = \frac{88}{2} = 44 \][/tex]
So, \(x = 44\).
#### 2.2.2. \(3x + 4 = 34\)
To isolate \(x\):
[tex]\[ 3x + 4 = 34 \implies 3x = 34 - 4 \implies 3x = 30 \implies x = \frac{30}{3} = 10 \][/tex]
So, \(x = 10\).
#### 2.2.3. \(4(x + 2) = 3(x + 2)\)
Let's simplify and solve for \(x\):
[tex]\[ 4(x + 2) = 3(x + 2) \implies 4 = 3 \][/tex]
There is no value of \(x\) that makes this equation true, so there is no solution.
#### 2.2.4. \(\frac{x}{3} + 2 = 5\)
To solve for \(x\):
[tex]\[ \frac{x}{3} + 2 = 5 \implies \frac{x}{3} = 5 - 2 \implies \frac{x}{3} = 3 \implies x = 3 \times 3 = 9 \][/tex]
So, \(x = 9\).
#### 2.2.5. \(3^x = 81\)
To solve for \(x\), note that \(81 = 3^4\):
[tex]\[ 3^x = 3^4 \implies x = 4 \][/tex]
So, \(x = 4\).
### 23. The sum of a number and 7 is 76. What is the number?
Let the number be \(y\). According to the problem:
[tex]\[ y + 7 = 76 \implies y = 76 - 7 = 69 \][/tex]
So, the number is 69.
This completes the step-by-step solution to the given algebra problem.
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.